Employment and Wage Effects of a Payroll-Tax Cut-Evidence from a Regional Experiment - Korkeamäki, Ossi; Uusitalo, Roope (Valtion taloudellinen tutkimuskeskus VATT, 2008)
In this paper we evaluate the effects of a regional experiment that reduced payroll-taxes by 3–6 percentage points for three years in Northern Finland. We match each firm in the target region with a similar firm in a comparison region and estimate the effect of the payroll-tax reduction by comparing employment and wage changes within the matched pairs before and after the start of the experiment. According to our results the reduction in the payroll-taxes led to an increase in wages in the target region. The point estimates indicate that the increase in wages offset roughly half of the impact of the payroll tax cut on the labor costs. The remaining labor cost reduction had no significant effects on employment. JEL-codes: J18, J23, J38, J58, J65, J6 Tutkimuksessa arvioidaan Lapin sotu-maksukokeilun työllisyysvaikutuksia. Kokeilu laski työn sivukuluja kolmeksi vuodeksi 3-6 prosenttiyksiköllä 14 Lapin kunnassa. Vaikutusarvio tehtiin vertaamalla kokeilualueen yritysten työllisyys- ja palkkamuutoksia vertailualueen yritysten muutoksiin ennen kokeilua ja kokeilun aikana. Vertailussa käytettiin kaltaistettujen parien menetelmää. Työn sivukulujen alentaminen johti kokeilualueen yrityksissä jonkin verran vertailualueen yrityksiä nopeampaan palkkojen nousuun. Palkkojen nousu vastasi noin puolta sotumaksujen alentamisen tuomasta työvoimakustannusten laskusta – jäljelle jäänyt työvoimakustannusten lasku ei johtanut työllisyyden kasvuun kokeilualueen yrityksissä. Asiasanat: Työnantajamaksut, työvoiman kysyntä, verotuksen kohtaanto, kaltaistetttujen parien menetelmä